Template-sacrificing synthesis of well-defined asymmetrically coordinated single-atom catalysts for highly efficient CO₂ electrocatalytic reduction - Huang, Ming (2022)
Although various single-atom catalysts have been designed, atomically engineering their coordination environment remains a great challenge. Herein, a one-pot template-sacrificing pyrolysis approach is developed to synthesize well-defined Ni-N4-O catalytic sites on highly porous graphitic carbon for electrocatalytic CO2 reduction to CO with high Faradaic efficiency (maximum of 97.2%) in a wide potential window (-0.56 to -1.06 V vs RHE) and with high stability. In-depth experimental and theoretical studies reveal that the axial Ni-O coordination introduces asymmetry to the catalytic center, leading to lower Gibbs free energy for the rate-limiting step, strengthened binding with *COOH, and a weaker association with *CO. The present results demonstrate the successful atomic-level coordination environment engineering of high-surface-area porous graphitic carbon-supported Ni single-atom catalysts (SACs), and the demonstrated method can be applied to synthesize an array of SACs (metal-N4-O) for various catalysis applications.